Aggravation of pulmonary diffusing capacity in highly trained athletes by 6 weeks of low-volume, low-intensity training - Galy, O.; Maimoun, L.; Coste, O.; Manetta, J.; Boussana, A.; Prefaut, C.; Hue, O. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Postexercise alveolar-capillary membrane-diffusing capacity (DLco) often decreases in highly trained endurance athletes and seems linked to their training status. To test the hypothesis that training status influences postexercise DLco, 13 male and 2 female triathletes (20.2 ± 4.4 y old, 175.2 ± 6.7 cm tall; weight in a range of 66.6 ± 7.4 kg to 67.4 ± 7.8 kg during the 1-y study) were randomized into experimental (n = 7) and control (n = 8) groups and performed VO2max cycle tests and simulated cycle-run successions (CR) of 30 min + 20 min after 3 periods in the competitive season. Methods: Both groups were tested before (pre-HTP) and after a 30-wk high-training period (HTP) with high training volume, intensity, and frequency. The experimental group was then also tested after a 6-wk low-training period (LTP) with low training volume, intensity, and frequency, while the control group continued training according to the HTP schedule for these 6 wk. Ventilatory data were collected continuously. DLco testing was performed before and 30, 60, and 120 min after the CR trials. Results: Whatever the period or group, DLco was significantly decreased 30 min after CR, with a significantly greater decrease in the experimental group than the control group in LTP (-15.7% and -9.3% of DLco, respectively). Conclusions: Six weeks of low training volume and intensity were sufficient to reverse the effects of high training volume and intensity on the alveolar-capillary membrane after a CR succession in competitive triathletes.